A Case of Poisoning with Abrus precatarius Complicated with Bilateral Basal Ganglia Haemorrhage - Arun Rajaratnam; Kishan Dissanayake; Kiertie Kularatne; Sunil Bowattage (Case Reports in Neurological Medicine)
Abrus precatarius is a tropical climber, whose seeds contain abrin, which is known to cause toxicity in humans. We report a case of a young girl, who presented with haemorrhagic enterocolitis, bilateral septal vein thrombosis, and basal ganglia haemorrhage leading to seizures and coma, following ingestion of toxic A. precatarius seeds. To the best of our knowledge, this is the first ever case to describe such an intracranial complication of abrin poisoning.